Prospective Science Teachers’ Self-Confidence in Computational Thinking Skills - Syafril, S.; Rahayu, T.; Ganefri, G. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aims to analyze prospective science teachers’ self-confidence in computational thinking skills on three main points: (i) prospective science teachers’ self-confidence in computational thinking skills, (ii) differences in prospective science teachers’ self-confidence in computational thinking skills as per gender, and (iii) differences in prospective science teachers’ self- confidence in computational thinking skills as per expertise (Biology and Physics). A quantitative cross-sectional survey methodology was used as the research design. A total of 1023 prospective science teachers (biology and physics) were randomly selected as the research sample from the 1959 total population. Data were collected using a self-confidence questionnaire on computational thinking skills. The adaptation results were assessed first by five experts before being tested on 74 prospective science teachers from different universities. The results show that prospective science teachers’ self-confidence in computational thinking skills was generally high (Mean = 78.57). The Mann-Whitney U test found no difference in prospective science teachers’ self-confidence in computational thinking skills as per gender (Mean= 78.05, SD= 9.03 for male, Mean= 78.73, SD= 6.86 for female, with a value of F= 6.028, Z= -0.891, Sig= 0.373 0.05). The Independent Sample t-test also showed no difference in prospective science teachers’ self-confidence in computational thinking skills as per expertise. This study concludes that prospective science teachers have high self-confidence in computational thinking skills as crucial skills in the science teaching profession.